ACTION SONG: PROMOTING A JOYFUL AND ENTERTAINING VOCABULARY LEARNING FOR KIDS - Dewi Anak Agung Istri Bulan; I Made Iwan Indrawan Jendra; Putu Santi Oktarina; I Dewa Gede Rat Dwiyana Putra; Komang Trisnadewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research aims to describe the best implementation of Action Songs in improving young learners’ body parts vocabularies mastery at ACCEL Kids Center Ubud. This is a CAR which has done in ACCEL Kids Center Ubud. There are 6 children who participate in this study because they have low vocabulary mastery especially in term of Body Parts. The findings of this research indicate the use of action songs as the best implementation of action songs as a media to improve young learners' body parts vocabulary mastery was the action songs that (1) could encourage young learners to focus and concentrate during the activity, (2) less of the materials that could distracted young learners coordination and concentration,(3) has the list of enough body parts vocabularies based, and (4) not too much words of intro lyric that not highlight to the core of vocabulary being taught. The teachers should use Action Song because it makes the situation of learning is enjoyment and entertaining. And enjoyment is the best primary modal that must be noticed as a way to get young learners' interest in learning. If the young learners have a high interest in the use of action songs, it might no longer be too challenging for teachers to carry the object lesson. Additionally, young learners may be able to open their thoughts on accepting the object lesson without problems.